Highly sensitive detection of nitrite by using gold nanoparticle-decorated α-Fe2O3 nanorod arrays as self-supporting photo-electrodes. Issue 6 (26th April 2019) - Kang, Shenghong; Zhang, Haimin; Wang, Guozhong; Zhang, Yunxia; Zhao, Huijun; Zhou, Hongjian; Cai, Weiping
Abstract : Gold nanoparticle (Au NP)-decorated-Fe2 O3 nanorod arrays (AuNPs-Fe2 O3 ) as a photoelectrode are applied to the detection of nitrite solution with a low limit of detection and high sensitivity. Abstract : Gold nanoparticle (AuNPs)-decorated α-Fe2 O3 nanorod arrays (AuNPs-Fe2 O3 ) were successfully fabricated by immersing hydrothermal-induced Fe2 O3 nanorod arrays into HAuCl4 solution, followed by a simple reduction process. The obtained AuNPs on the α-Fe2 O3 nanorods were about 3–5 nm in diameter. The photocurrent of AuNPs-Fe2 O3 was twice as large as that of α-Fe2 O3 nanorods. Benefiting from the good photoelectric properties, the proposed AuNPs-Fe2 O3 can be directly utilized as a self-supporting photoelectrode for nitrite detection. As a result, the as-constructed sensor exhibited good photoelectron catalytic activity and selectivity, high sensitivity (0.1736 ± 0.01 μA μM −1 cm −2 ) and a low limit of detection (0.07 μM). The current response has a high linear correlation ( R ≥ 0.999) in a wide range from 1 μM to 1000 μM and high stability. In addition, the as-constructed sensor was further employed for nitrite detection in tap and rain water samples to evaluate its practical applications.